Metals Content of Roadside Soils in Riyadh (Saudi Arabia), with Particular Reference to Traffic Density - Al-Shayeb, S.M. (Asian Journal of Chemistry, 2010)
The metals content (Pb, Zn, Cu, Cr, Ni and Li) of roadside surface and subsurface soils was determined along the major roads and highways in Riyadh city. Their levels were investigated in relation to traffic loads. Results showed that enhanced levels of Pb, Zn, and Cu correlated well with traffic density. Cr correlated well with Pb indicating the same source. No evidence of Ni contamination of roadside soils was obtained. Concentrations of Pb, Zn and Cu in soil showed enrichment in the upper surface soils, which is attributed to the low rainfall in the study area An important source of lead is the combustion of leaded gasoline used for transportation in Saudi Arabia.